The role of LAZISMU in eradicating poverty in D.I. Yogyakarta - Syaputra, Ahmad Danu (Journal of Islamic Economics Lariba, 2016)
Zakat is one of economic empowerment instruments that is defined as giving someone his right. And the demand is to have the financial balance, not the accumulation of wealth in a particular group. To realize this idea in the society, LAZISMU as Amil Zakat Institution must empower the economics of the society to eradicate poverty. The method used in this study is qualitative by analyzing data from interview to LAZISMU board. Besides, the gathering data technique is also done by documentation. Once the data collected, they are processed and analyzed descriptively qualitative. The results of this study indicate that efforts to alleviate poverty conducted by LAZISMU in Yogyakarta have shown a significant role since they cooperate with Muhammadiyah Institutions that in fact has been very experienced and already has a wide range.